Identifying Patient-Centered Outcomes for Caregivers and Children With Musculoskeletal Infections. (12th December 2022) - Wood, James B; Hawryluk, Bridget; Lynch, Dustin; Claxton, Gina; Russell, Kelsey; Bennett, William E; Wiehe, Sarah E; Carroll, Aaron E
Abstract: Background: Musculoskeletal infections (MSKI), including osteomyelitis and septic arthritis, are among the most common invasive infections in children and have the potential to cause significant morbidity. Guidelines have been developed to optimize care based on clinician-developed endpoints. Patient-centered outcomes have not been defined for children with MSKI. This study identified outcomes most important to caregivers and patients with MSKI. Methods: This was a single-center prospective qualitative study of children 6 months to 18 years of age hospitalized with MSKI from November 2019 to September 2021. Using design-research methods, patients and caregivers participated in interviews and/or completed journals to describe their experiences during acute infection and recovery from MSKI. Results: A total of 51 patient/caregivers were approached to participate in the study, 35 of whom declined to participate, resulting in 8 interviews conducted and 14 journals collected from 16 patient/caregivers. From these, a journey map was created highlighting points of stress during the onset of symptoms, through hospitalization, and returning home with new challenges. In addition, patient-centered outcomes were identified. For caregivers, these included managing mental health, managing responsibilities, and receiving support. Both caregivers and patients shared the importance of understanding of treatment plans and responsibilities. For patients, improving mental and physical health was important. Conclusions: Management of children with MSKI is complex and requires a multidisciplinary team approach. Validation of the outcomes identified and development of a measurement tool are needed. Addressing the patient-centered outcomes we identified in this study can greatly improve the holistic care of children with MSKI. Abstract : Using design-research methods, we identified patient-centered outcomes for caregivers and children with MSKI. Outcomes included managing mental health, managing responsibilities, and receiving support for caregivers, shared understanding of treatment plans and responsibilities, improving mental and physical health of the patient.